2012
DOI: 10.5573/jsts.2012.12.4.458
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Modeling and Simulation for Dual Metal Gate Stack Architecture (DMGSA) Cylindrical/Surrounded Gate MOSFET

Abstract: Abstract-A Dual metal gate stack cylindrical/ surrounded gate MOSFET (DMGSA CGT/SGT MOSFET) has been proposed and an analytical model has been developed to examine the impact of this structure in suppressing short channel effects and in enhancing the device performance. It is demonstrated that incorporation of gate stack along with dual metal gate architecture results in improvement in short channel immunity. It is also examined that for DMGSA CGT/SGT the minimum surface potential in the channel reduces, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Therefore, to lower down SCE's, engineering of placing the dielectric material is required. A high K dielectric concept has been implemented in conventional cylindrical surrounded MOS by the authors in [51,53]. The material having a low dielectric constant can be placed at the drain end whereas high dielectric material is placed at the source end.…”
Section: High-k Dielectric Based Structurementioning
confidence: 99%
“…Therefore, to lower down SCE's, engineering of placing the dielectric material is required. A high K dielectric concept has been implemented in conventional cylindrical surrounded MOS by the authors in [51,53]. The material having a low dielectric constant can be placed at the drain end whereas high dielectric material is placed at the source end.…”
Section: High-k Dielectric Based Structurementioning
confidence: 99%
“…However it is achieved at the cost of current drivability and gain. In order to improve the device operation characteristics, high-k dielectric [22,23] has been widely incorporated as a gate stack. Ghosh et al [23] showed that gate stack architecture with a high-k dielectric on a dual metal CSG MOSFET device decreases the minimum surface potential of the device, which consequently increases the carrier transport efficiency and prevents the direct tunneling leakage current.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the device operation characteristics, high-k dielectric [22,23] has been widely incorporated as a gate stack. Ghosh et al [23] showed that gate stack architecture with a high-k dielectric on a dual metal CSG MOSFET device decreases the minimum surface potential of the device, which consequently increases the carrier transport efficiency and prevents the direct tunneling leakage current. Although the use of asymmetric gate stack [24,25] has been studied in the past, the same has not been incorporated on a JL MOSFET.…”
Section: Introductionmentioning
confidence: 99%
“…Gate material engineering (GME) is one of them proposed by Chiang et al [12] and Kumar et al [13]. In GME technique, gate metal work function is tuned so that the metal with high work function accelerates charge carriers near the source region while the low work function metal is chosen at drain region [14], [15]. These expedited charge carriers collected at drain region provide higher ION.…”
Section: Introductionmentioning
confidence: 99%